EVALUASI PROGRAM PENDIDIKAN DAN PENGEMBANGAN ANAK USIA DINI (PPAUD) DI KABUPATEN KULON PROGO - Herdi Handoko; Wuradji Wuradji (Universitas Negeri Yogyakarta, 2015)
This study aimed to (1) determine the effectiveness of the Early Childhood Education and Development Program (ECED) to the increase in access to early childhood education services in Kulon Progo, (2) determine the effectiveness of the Early Childhood Education and Development Program (ECED) to improve the quality of early childhood education services in Kulon Progo. This research is a qualitative evaluation study. That approach used in the research is CIPP model evaluation program develop by Stufflebeam. The results of the study revealed that: (1) The Early Childhood Education and Development Program (ECED) in Kulon Progo Regency has been able to improve access to early childhood education services as evidenced by an increase of 34.3% APK in 2006 increased to 93.6% in 2013. (2) the Early Childhood Education and Development Program (ECED) in Kulon Progo Regency has been able to improve the quality of early childhood education services